See the picture :D. Please help fast.
![See the picture D Please help fast class=](https://us-static.z-dn.net/files/ded/973e2c6d3712bd7ffcdca3c0625ccc3c.jpg)
Answer:
In ΔABD and ΔAEC
BE=DC (given) …(i)
Subtracting DE from both side of (i), we get
BE–DE=DC–DE
BD=EC
AB=AC (given)
∠B=∠C (angle opposite to equal sides are equal)
Similarly, ΔABD≅ΔAEC
AD=AE (by c.p.c.t)
Hence proved
Answer:
Step-by-step explanation:
Consider triangles ABE and ACD:
According to above congruence statements, we can conclude:
Since the triangles are congruent, we have: